2006
DOI: 10.1111/j.1468-2982.2005.01077.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Pharmacological Treatment of Migraine Patients Referred to Headache Specialists in Canada

Abstract: We set out to examine selected clinical characteristics of migraine patients referred to neurologists specializing in headache in Canada, and to document their pharmacological therapy both before and after consultation with the neurologist. Demographic, clinical and pharmacotherapy data were collected at the time of consultation for 606 patients referred to five headache clinics and who were given a migraine diagnosis by the neurologist. Data were analysed as part of the Canadian Headache Outpatient Registry a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 48 publications
0
35
1
1
Order By: Relevance
“…In a Canadian study, 606 migraine patients referred to neurologists specializing in headache showed that only 7.6% used anti-emetic drugs before referral, and almost 19% after consultation. However, the study did not clearly state which patients had an indication for treatment with anti-emetics (8). It seems that nausea and vomiting in migraine patients are undertreated phenomena, although guidelines recommend the prescription of anti-emetics.…”
Section: Discussionmentioning
confidence: 97%
“…In a Canadian study, 606 migraine patients referred to neurologists specializing in headache showed that only 7.6% used anti-emetic drugs before referral, and almost 19% after consultation. However, the study did not clearly state which patients had an indication for treatment with anti-emetics (8). It seems that nausea and vomiting in migraine patients are undertreated phenomena, although guidelines recommend the prescription of anti-emetics.…”
Section: Discussionmentioning
confidence: 97%
“…К сожалению, лечение мигрени обыч-но не оптимально, так как не назначаются триптаны и про-филактическая терапия [37,38].…”
Section: о б з о р ыunclassified
“…According to estimates, about 25% of all migraine sufferers should be offered prophylactic therapy, 7 and prophylactic medications are thought to be underutilized. 5 When migraine prophylactic therapy is started, one of three outcomes can be anticipated. The patient may show substantial benefit, which is usually defined as a reduction in frequency of headaches of 50% or more.…”
Section: Prophylaxis Of Migraine Headachementioning
confidence: 99%
“…1,4 The Canadian Headache Outpatient Registry and Database Project found that 21% of patients with a diagnosis of migraine who were referred to headache specialists had symptomatic medication overuse. 5 When prophylaxis should be started is a matter of clinical judgement. Evidence on which to base this decision is lacking, and many medications are available from which to choose.…”
Section: The Casementioning
confidence: 99%